2014
DOI: 10.1177/0194599814526561
|View full text |Cite
|
Sign up to set email alerts
|

Societal‐level Risk Factors Associated with Pediatric Hearing Loss: A Systematic Review

Abstract: Objective To determine if the current body of evidence describes specific threshold values of concern for modifiable societal-level risk factors for pediatric hearing loss, with the overarching goal of providing actionable guidance for the prevention and screening of audiological deficits in children. Data Sources Three related systematic reviews were performed. Computerized PubMed, Embase, and Cochrane Library searches were performed from inception through October 2013 and were supplemented with manual sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The percentage of deaf people who had access to university education in this study (2%) was similar to the 5% reported by Blanchfield et al 19 in the United States. Furthermore, the higher prevalence of prelingually deaf people in the lowest income quintiles corroborates the results found in a systematic review about societal-level risk factors associated with pediatric hearing loss 22 .…”
Section: Socioeconomic Gradientsupporting
confidence: 85%
“…The percentage of deaf people who had access to university education in this study (2%) was similar to the 5% reported by Blanchfield et al 19 in the United States. Furthermore, the higher prevalence of prelingually deaf people in the lowest income quintiles corroborates the results found in a systematic review about societal-level risk factors associated with pediatric hearing loss 22 .…”
Section: Socioeconomic Gradientsupporting
confidence: 85%
“…provincial and central levels), but a number of health services that used to be delivered at higher-level facilities are gradually becoming available at the district and commune levels. The health reports ( Orb et al, 2014 ; Waters et al, 2016 ) have indicated that curative services at the grassroots level have failed to attract people or gain their trust. Several studies have shown patients’ dissatisfaction with the facilities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A sister article focuses on risk factors that are more likely to require societal-level changes for modification. 29 …”
Section: Introductionmentioning
confidence: 99%